The Influence of Price, Product Quality, and Content Marketing, on Purchasing Decisions in Tiktok Shop E-Commerce (Case Study on Wiraraja University Students, Sumenep) - Sofia Nur Afifah; Rusnani Rusnani (Nomico, 2024)
TikTok launched the TikTok Shop feature so that it can continue its mission to make its users happy by making shopping easy without the need to switch software. This research aims to determine the contribution of price, product quality and content marketing to purchasing decisions at the TikTok Shop (case study of Wiraraja University students. To answer this problem, the type of research used is a quantitative method with 80 respondents taken, sampling technique using purposive sampling by distributing questionnaires. The data analysis techniques used are descriptive statistical tests, research instrument tests (validity and reliability tests), classical assumption tests (normality, heteroscedasticity, multicollinearity and linearity tests), multiple linear regression equation tests and hypothesis tests (t test). , F test, coefficient of determination). The results of this research show that product quality and content marketing influence purchasing decisions at TikTok Shop according to the t test which states that partially product quality and marketing content have a significant influence on purchasing decisions, while price partially has no influence on purchasing decisions.